Ichthyosis follicularis syndromes in patients with mutations in GJB2. (23rd June 2022) - Youssefian, Leila; Naji, Mahtab; Park, Jason S.; Rajabi, Fateme; Abdollahimajd, Fahimeh; Mahmoudi, Hamidreza; Kamyab‐Hesari, Kambiz; Ghalamkarpour, Fariba; Zabihi, Masoud; Teimoorian, Mehrdad; Youssefian, Laya; Zeinali, Sirous; et al.
Abstract: Ichthyosis follicularis (IF) manifests as generalized spiny follicular projections found in syndromic diseases secondary to SREBF1 and MBTPS2 mutations. We sought the genetic cause of IF in two distinct families from a cohort of 180 patients with ichthyosis. In Family 1, the proband (Patient 1) presented with IF, bilateral sensorineural hearing loss and punctate palmoplantar keratoderma. Using DNA from peripheral blood lymphocytes, two compound heterozygous mutations, c.526A>G and c.35delG, were discovered in GJB2 . In Family 2, the proband (Patient 2) presented with a previously unreported IF phenotype in the context of keratitis–ichthyosis–deafness syndrome, and whole‐exome sequencing found a de novo heterozygous mutation, c.148G>A in GJB2 . Histopathology was consistent with porokeratotic eccrine ostial and dermal duct naevus (PEODDN) and IF in Patients 1 and 2, respectively. Our findings add to the clinical and histopathological spectrum of IF and emphasize the association of PEODDN‐like entities with GJB2 variants. Abstract : We sought the genetic cause of ichthyosis follicularis (IF) in two distinct patients with syndromic ichthyosis: one with the triad of IF, bilateral sensorineural hearing loss and punctate palmoplantar keratoderma, and the other with a previously unreported IF phenotype in the context of keratitis–ichthyosis–deafness syndrome. Mutations in GJB2 were discovered in both patients. Histopathology of skin samples was consistent with porokeratotic eccrine ostial and dermal duct naevus (PEODDN) in Patient 1 and with IF in Patient 2. Our findings add to the clinical and histopathological spectrum of IF and emphasize the association of PEODDN‐like entities with GJB2 variants.